PENDIDIKAN KEWARGANEGARAAN DALAM LITERASI DAN PARTISIPASI POLITIK GENERASI MUDA - Muci Herliyanto; Nurdian Setiawan; Vinni Helvionita (STKIP Subang, 2025)
This research aims to reveal the process of implementing Civic Education in shaping political literacy and participation among young people at the research site, as well as identifying the factors underlying its optimal success, given that these outcomes differ from the general tendency of low youth political literacy and participation widely reported in various studies. The research employs a qualitative approach with a case study design, using observation, in-depth interviews, and documentation study, analyzed through an interactive analysis model and strengthened by source and technique triangulation. The results show that contextual and participatory civic education learning is able to build mature political understanding alongside genuine youth involvement in democratic life. This success is supported by three main factors: the quality of learning interaction that opens space for critical dialogue, consistent involvement in real civic activities, and a social environment that supports openness in expressing opinions. These findings confirm that the success of civic education depends on the design of the learning process itself, rather than merely the existence of a curriculum, while also contributing to the achievement of the SDGs through the strengthening of education quality and youth democratic participation.